HUBUNGAN DUKUNGAN KELUARGA TERHADAP KEMANDIRIAN ANAK TUNAGRAHITA DALAM MENGHADAPI MENARKE - Wieke Maulidia; Juniar Ernawaty; Siti Rahmalia Hairani Damanik (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Menarche is a natural and normal thing experienced by every woman. Independence is needed by a woman in facing menarche. The family is a supporter of someone in facing it. This study aimed to determine the relationship between family support and the independence of mental retardation children facing menarche. The design of this research was a Correlation Research by applying retrospective method. The location was in the State Special Schools Nurture Pekanbaru because this school had the highest number of retarded students in Pekanbaru which were 306 students. The sample contained 35 respondents who fit to the inclusion criteria. The instruments used were family support and selfreliance questionnaires that were made by the researcher and had been tested for its validity and reliability. The analysis used were univariate analysis to determine the frequency distribution and bivariate by using the chi-square test. The results showed that 11 respondents (31.4%) displayed negative family support with low independence and 13 respondents (37.1) demonstrated positive family support with high independence. The results of the chi-square test indicated that the p value -0.028 <α = (0.05) it concluded that there was a significant relationship between family support for the independence of children with mental retardation in facing menarche. For people who have family members with mental retardation, families can provide support for mentally retarded children to improve the independence of mentally retarded children to face menarche even though the child has limited abilities. Keywords: Family Support, Menarche, Mental Retardation